Économie de la « société de l’information » Quoi de neuf ? - Félix Weygand (Tic & Société)
The ideology of the "information society" is based on an economic story. This story discovers a "new economy" characterized by "dematerialization" whose the two consequences would be the "piracy" of works and the development of “Web 2.0 media" based on the direct management of information by the public. These four "discoveries" of the economic ideology of the information society are refuted not only on the theoretical level but also by a case study of an Internet-based firm (Cityvox). The real changes that affect the economy of informational goods in relation to the development of digital technologies can be described as a contemporary manifestation of capitalist and industrial economy principles, regarding the development and transfer of value and competition between firms.